Efficacy and Safety of Microsurgery in Interdisciplinary Treatment of Sarcoma Affecting the Bone - Zeller, Johannes; Kiefer, Jurij; Braig, David; Winninger, Oscar; Dovi-Akue, David; Herget, Georg W.; Stark, G. B.; Eisenhardt, Steffen U. (Frontiers in Oncology, 2019)
BACKGROUND: Sarcomas are tumors of mesenchymal origin with high variation in anatomical localization. Sarcomas affecting the bone often require an interdisciplinary resection and reconstruction approach. However, it is critical that microsurgical reconstruction strategies do not negatively impact tumor safety and overall survival, as limb salvage is only the secondary goal of tumor surgery. Here, we analyzed the efficacy and safety of microsurgery in interdisciplinary treatment of sarcoma affecting the bone. PATIENTS AND METHODS: We performed a retrospective chart review of all patients treated for soft-tissue and bone sarcoma at the senior author’s institution with a focus on bone affection and microsurgical reconstruction between 2000 and 2019. This particular subgroup was further investigated for tumor resection status, 5-year survival rate, length of hospital stay, as well as overall complication and amputation rates. RESULTS: Between 2000 and 2019, 803 patients were operated for sarcoma resection and reconstruction by the Department of Plastic and Hand Surgery. Of these, 212 patients presented with sarcoma of the extremity affecting the bone. Within this subgroup, 40 patients required microsurgical reconstruction for limb salvage, which was possible in 38 cases. R0 resection was achieved in 93.8 %. The 5-year survival was 96.7 %, and the overall complication rate was 25 %, of which 40 % were microsurgery associated complications. CONCLUSION: Safe and function-preserving treatment of soft-tissue and bone sarcoma is challenging. Primary reconstruction with microsurgical techniques of sarcoma-related defects enables limb-sparing and adequate oncosurgical cancer treatment without increasing the risk for local recurrence or prolonged hospital stay. The treatment of sarcoma patients should be reserved to high-volume centers with experienced plastic surgeon embedded in a comprehensive treatment concept.